2008
DOI: 10.1002/app.28737
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications of poly(vinyl alcohol)‐congo red aqueous solutions and hydrogels as liquids for hydraulic fracturing

Abstract: The authors report on the viscoelastic characterization of guar hydrogels obtained through complexation reactions with borax ions. These gels are compared with hydrogels obtained from poly(vinyl alcohol) of different degree of hydrolysis through complexation reactions with congo red. The effect of the degree of hydrolysis and both, the concentration of PVA and the concentration of congo red, on the viscoelastic properties of the hydrogels is analyzed. The potential use of the PVA-based hydrogels as hydraulic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[42] Also, the authors explored different synthetic methodology to obtain other series of copolymers (3) which are summarized in the Figure 5. [43][44][45] Alternatively, Vega et al described the synthesis of copolymers with 1,3-isoxazole groups pendant groups from hydro- lyzed polyacrylamide (HPAM), a polymer of variety and different applications in oil gas industry. [46] In oil industry, hydrogels are widely used in drilling operations or in well stimulation treatments, also as water shutoff and as loss control materials (LCM).…”
Section: Materials For Oil and Gas Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…[42] Also, the authors explored different synthetic methodology to obtain other series of copolymers (3) which are summarized in the Figure 5. [43][44][45] Alternatively, Vega et al described the synthesis of copolymers with 1,3-isoxazole groups pendant groups from hydro- lyzed polyacrylamide (HPAM), a polymer of variety and different applications in oil gas industry. [46] In oil industry, hydrogels are widely used in drilling operations or in well stimulation treatments, also as water shutoff and as loss control materials (LCM).…”
Section: Materials For Oil and Gas Industrymentioning
confidence: 99%
“…Treatment of the PAN with different acyl chlorides produced terpolymers with tetrazole, cyano and 1,3,4‐oxadizoles pendant groups ( 2 ), which were soluble in polar solvents and presented interesting rheological behavior that allow their use as FF in underground formations [42] . Also, the authors explored different synthetic methodology to obtain other series of copolymers ( 3 ) which are summarized in the Figure 5 [43–45] …”
Section: Materials For Oil and Gas Industrymentioning
confidence: 99%
“…PVA is a versatile polymer that can suffers chemical modification or physical interactions that lead to new materials with improved properties; for example, Vega et al have reported stiff gels by PVA and Congo red interaction that can be used as hydraulic fracturing liquids [1]. Moreover, attempt was made to prepare an interpenetrated network hydrogel microsphere by using PVA and locust bean gum for oral controlled drug delivery [2].…”
Section: Introductionmentioning
confidence: 99%
“…Blocking gels have been used in low‐temperature formations for many years. However, certain problems have been associated with isolating high‐temperature subterranean zones, principally due to insufficient viscosity and stiffness of the crosslinked blocking gels 2, 3…”
Section: Introductionmentioning
confidence: 99%
“…Values of 2000 cp or higher must be achieved to consider a plug as efficient. It is assumed that high viscosity values will provide low‐fluid leak‐off properties 3–5…”
Section: Introductionmentioning
confidence: 99%